Ultrafast pore-tailoring of dense microporous carbon for high volumetric performance supercapacitors in organic electrolyte. (May 2022) - Li, Qiqi; Jiang, Yuting; Jiang, Zimu; Zhu, Jiayao; Gan, Xuemeng; Qin, Fuwei; Tang, Tingting; Luo, Wanxia; Guo, Nannan; Liu, Zheng; Wang, Luxiang; Zhang, Su; et al.
Abstract: Preparing activated carbon with high volumetric performance in organic electrolyte is crucial for developing high-energy and miniaturized supercapacitors, but still challenging because high surface area and large pore size are required to effectively store large-sized organic electrolyte ions, which usually result in the low density. Herein, an ultrafast strategy is proposed to tailor the interconnected porous structure of activated carbon through introducing CO2 at the end of homogeneous activation. The uniformly distributed potassium components in carbon matrix promote a robust catalytic etching by CO2, leading to precise tailoring of the ultramicropores (0.50–0.72 nm) to large micropores (0.81–1.14 nm) within only 2 min. The optimized sample with both high surface area and compaction density (2147 m 2 g −1, 0.68 g cm −3 ) shows high gravimetric and volumetric capacitances (155 F g −1 and 106 F cm −3 at 1 A g −1 ) as well as good rate performance (102 F g −1 and 70 F cm −3 at 20 A g −1 ) in organic electrolyte. The symmetric supercapacitor achieves high energy densities of 35 Wh kg −1 and 24 Wh L −1 at 573 W kg −1 and 395 W L −1, respectively, indicating great potential of the ultrafast tailoring strategy for practical application. Graphical abstract: Introducing CO2 at the end of homogeneous activation for only 2 min effectively tailors the porous structure of activated carbon, leading to high gravimetric and volumetric capacitance as well as robust kinetics for supercapacitors in organic electrolytes. Image 1 Highlights: An ultrafast strategy is developed to tailor porous structure of activated carbon. The tailored porous structure enables both high surface area and density. The sample shows outstanding capacitive performance in organic electrolyte. Robust electrochemical kinetics is maintained at high electrode mass loadings.